Investigation for the Temperature Dependence of 2D Electron Gas Behaviors in GaN‐based Multichannel Heterostructures Systems - Wentao Zhang; Ang Li; Chong Wang; Kai Liu; Kuo Zhang; Xuefeng Zheng; Xiaohua Ma; Yue Hao (Advanced Materials Interfaces)
Abstract In this study, 2 electron gas(2DEG) behaviors in Al0.28Ga0.72N/GaN multichannel heterostructures with doped and undoped barrier layers and lattice‐matched In0.10Al0.40Ga0.50N/GaN multichannel heterostructures are investigated. Within the temperature range of 300–425 K, the sheet resistance of the Al0.28Ga0.72N/GaN heterostructures increased 2.5 times, while the sheet resistance of the In0.10Al0.40Ga0.50N/GaN heterostructures increased only nearly 2 times. The mobility of 2DEG in different channels extracted by I–V curves at different temperatures indicated that the mobility of 2DEG of the bottom channel is susceptible to the temperatures due to weak confinement. And the capacitance–voltage (C–V) curves demonstrated that the 2DEG behaviors in three channels are different as well. By analyzing the 2DEG behaviors in different channels and energy band of the heterostructures, it is the large conduction band difference and matched lattice constant that endow In0.10Al0.40Ga0.50N/GaN better performance to withstand the band narrowing effect, which caused quantum well shallowing and the 3D transformation of 2DEG. The results provid the reference for fabricating the GaN‐based devices with higher temperature stability.